The evaluation of the antimicrobial properties of biodegradable prodrugs with chlorphenesin - Sebai, Agnieszka; Ruśkowski, Paweł; Gadomska-Gajadhur, Agnieszka; Mierzejewska, Jolanta; Kruk, Aleksandra; Synoradzki, Ludwik (Polimery, 2021)
Spheres of prodrug of polylactide (PLA) or polycaprolactone (PCL) or a copolymer thereof with chlorphenesin (CF) were obtained. Furthermore spheres with an active substance additionally dispersed in the prodrug matrix – hybrid spheres – were prepared. The antimicrobial properties of the prodrug forms obtained were investigated towards bacteria, yeast, and filamentous fungi to verify whether the CF activity of the new formulations maintains. This research shows a wide spectrum of antimicrobiological application, especially when using CF as a preservative.